Enchancement of Toremifene Anti-Tumor Action by Metformin and Unusual Side Effect of Toremifene in Male Transgenic Mice with HER2-Positive Breast Tumor - Stukov, Alexander N.; Osipov, Mikhail A.; Semiglazova, Tatjana Y.; Filatova, Larisa V.; Alexandrov, Valerij A.; Bespalov, Vladimir G.; Semenov, Alexander L.; Tyndyk, Margarita L.; Yurova, Maria N.; Panchenko, Andrey V.; Baranenko, Denis A. (Drug Research, 2019)
HER2-positive breast tumors are found in 25–30% of patients with breast cancer and are characterized by aggressive course and reduced sensitivity to both chemotherapy and hormone therapy. The aim of the work was to study the possibilities of enhancing the therapeutic effect of anti-estrogen drug toremifene by combining it with biguanide, metformin, on the HER2-positive breast cancer model in FVB/N HER-2/neu transgenic mouse. Male FBV/N mice with intramuscularly transplanted HER2-positive mammary gland tumor from a female mouse of the same strain have been given toremifene (30 mg/kg, orally daily) or metformin (100 mg/kg, orally daily) that had a moderate antitumor effect (decrease the area under the kinetic curve of tumor growth by 1.6 and 1.5 times, respectively, when compared with intact control). Co-administration of these drugs in the same doses had a more pronounced effect (the area under the kinetic curve of tumor growth decreased by 3.1 times compared to intact control; p<0.05). After 10 days, in group receiving toremifene all 10 mice developed inguinal-scrotal hernias, and in group that received toremifene plus metformin - only 5 of 10 (p=0.0325). By the 15th day after the start of treatment, the hernias was also determined in all mice treated with the combination of toremifene and metformin, but the size of the hernial sac was significantly smaller than in those receiving only toremifene - 537 ± 96 mm3 and 1309 ± 120 mm3, respectively (p=0.0001). A possible explanation is the manifestation of collagen-degrading effect of toremifene.
Keywords: toremifene; metformin; breast cancer; FVB/N HER-2/neu mice; hernia; antitumor effect